A conceptual enzyme-cell therapy model to aid microplastic clearance from the vitreous humor - Corridon, Peter R.; Almansoori, Meera; Alshamsi, Sara; Almazrouei, Shaikha; Papadakis, Raffaello (Frontiers in Bioengineering and Biotechnology, 2026)
Ultrafine plastic microparticles have been detected in ocular compartments, raising concern about their role in degenerative eye diseases. Nevertheless, significant efforts are required to elucidate the underlying pathophysiological mechanisms that govern their accumulation and persistence. Among the various ocular compartments, the vitreous humor (VH) is particularly susceptible due to its immune privilege and limited clearance capacity. In this conceptual study, we propose turning these physiological constraints into a therapeutic opportunity. We outline potential mechanistic routes through which ultrafine particles infiltrate and accumulate within the VH, contributing to tissue degradation, and simultaneously introduce a novel injectable enzyme-cell therapeutic model designed to mitigate and reverse these effects. The proposed injectable platform employs postmortem-derived VH as a biomimetic vehicle incorporating polyethylene terephthalate (PET)-degrading enzymes (e.g., mPETase) and genetically engineered hyalocytes expressing mono(2-hydroxyethyl) terephthalate hydrolase (MHETase), terephthalic acid dioxygenase (TPADO), and glycol oxidase (GOx). These enzymes collectively catalyze the breakdown of PET into benign metabolites, facilitating localized detoxification, while the VH-based hydrogel scaffold supports the in situ ocular structural reconstitution. Hyalocytes further enhance matrix integration and phagocytic clearance. This work presents a conceptual framework rather than experiential validation, defining a multimodal strategy that may serve as a foundation for future therapies aimed at combating ocular plastic toxicity and informing broader regenerative approaches to microplastic detoxification in immune-privileged tissues.